I. Quantification by Double-Isotope Parametric Scintigraphy - Als, Claudine; Listevnik, Maria; Rösier, H.; Ritter, E.-P. (Nuklearmedizin - NuclearMedicine, 1995)
A new quantitative subtraction method of thyroid scans is proposed which shows that regional function (F) by far exceeds regional cellularity or cell density (C) in potentially toxic thyroidal areas of non-immunogenic hyperthyroidism (NIH). Methods: A multistep processing of radioiodine and MIBI thyroid scans of patients with non-immunogenic hyperthyroidism led to normalized images of regional function excess and of perinodular enhancement. Two numeric factors were derived from regions of interest: Q (cell density ratio) comparing MIBI uptake in autonomous and suppressed areas and T (toxicity index): the maximal F/C contrast. Results: Q never exceeded 61; T, however, expanded toxicity levels over a range of 6-8735 with toxic adenomas (median = 165) and with hot areas of multifocal functional autonomy (median = 15). T was weakly correlated to serum TT3 (r = 0.41), but not to autonomous tissue mass, ultrasonographic or cytologic criteria. Conclusions: T is governed by inherent features of autonomous tissue and the response of the imbedded thyroid tissue to TSH stimulation. This standardized technique consolidates experiences from visual analysis; the huge T range mirrors the natural evolution from compensated autonomy towards hyperthyroid, decompensated stages.
Keywords: Non-immunogenic hyperthyroidism; cell density; autonomous function; double-isotope scintigraphy; 99mTc-Hexamibi